Policy preferences and policy legitimacy after referendums: Evidence from the Brexit negotiations - Hobolt, S; Tilley, J; Leeper, T (Springer, 2020)
How do votes in direct democratic ballots translate into policy preferences about future outcomes and affect the perceived legitimacy of those outcomes? This article examines these questions in the context of sovereignty referendums: specifically, the 2016 referendum on British membership of the European Union (EU). While the referendum result gave the British government a mandate for Britain leaving the EU, it did not provide any firm guidance as to the kind of Brexit that voters would prefer and consider legitimate. To examine the perceived desirability and legitimacy of different Brexit outcomes, we conducted a nationally representative conjoint experiment measuring attitudes towards different possible negotiation outcomes. Our findings show that ‘Leave’ and ‘Remain’ voters were highly divided over what they wanted from Brexit on salient negotiation issues, but also that most voters did not regard any possible outcome as legitimate.